Rational curves in holomorphic symplectic varieties and Gromov-Witten invariants - Oberdieck, Georg; Shen, Junliang; Yin, Qizheng (Advances in mathematics, 2019)
We use Gromov-Witten theory to study rational curves in holomorphic symplectic varieties. We present a numerical criterion for the existence of uniruled divisors swept out by rational curves in the primitive curve class of a very general holomorphic symplectic variety of K3[n] type. We also classify all rational curves in the primitive curve class of the Fano variety of lines in a very general cubic 4-fold, and prove the irreducibility of the corresponding moduli space. Our proofs rely on Gromov-Witten calculations by the first author, and in the Fano case on a geometric construction of Voisin. In the Fano case a second proof via classical geometry is sketched.
Gesehen am 14.01.2025